Evaluation of different artificial light technologies for indoor aquaponic production of Bibb lettuce, Lactuca sativa var. capitata, and compact basil, Ocimum basilicum var. Genovese. Issue 3 (26th November 2021) - Shultz, R. Charles; Coyle, Shawn D.; Bright, Leigh Anne; Hager, Janelle V.; Tidwell, James H.
Abstract: Aquaponic production in temperate climates is often conducted in insulated buildings to reduce heating costs and therefore must rely on artificial lighting to replace natural sunlight. However, there are several different light technologies available to producers. We conducted two aquaponic growth trials to compare four lighting technologies for the indoor production of Bibb lettuce, Lactuca sativa var. capitata (Trial 1), and basil, Ocimum basilicum var. Genovese (Trial 2). Light types evaluated included metal halide (MH), fluorescent (FLO), light‐emitting diode (LED), and induction (IND). Using a complete block design, each of the four identical aquaponic systems included all four light types. Juvenile Nile tilapia, Oreochromis niloticus, (Trial 1:145 g; Trial 2:169 g) were stocked into each replicate system and fed at a rate of 60 g feed m −2 of plant grow‐space per day. In Trial 1, Bibb lettuce plants grown under LED lights had significantly higher ( p  ≤ 0.05) average individual weights (164 g), higher production per unit area (3118 g m −2 ), and higher production per unit energy (84 g m −2 kWh −1 ) compared to those grown under the other light types. Bibb lettuce grown under IND and FLO lights had significantly higher ( p  ≤ 0.05) average individual weights (82.0 and 78.0 g, respectively) and production per unit of area (1762 and 1700 g m −2, respectively) than those grown under MH lights (1382 g m −2 ). In Trial 2, Basil grown under LED lights had significantly higher ( p  ≤ 0.05) average individual weights (188 g), production per unit area (4970 m −2 ), and production per unit of energy (1483 g m −2 kWh −1 ) than basil grown under the other three light types. There was no significant difference ( p  > 0.05) in average individual weight or production per unit area among basil plants grown under MH, IND or FLO. Analysis of leaf tissues indicated several statistically significant differences among the light treatments. However, the actual magnitudes of these differences were relatively small. Evaluation of emitted wavelengths indicate that production differences may be related to the amount of red light spectra (600–699 nm), and the ratio of red light to blue light (400–499 nm) (R:B ratio) produced by the different light types. The LED had a greater production of red spectra and higher R:B ratios than other lights which appears to be advantageous for growth of Bibb lettuce and basil.